The Individual, Organizational and Social Contexts of Teleworking and Technostress during Covid-19 Pandemic: A Holistic Analysis based on JD-R Model - Marco Valeri; Kasım Subaşı; Nuray Akar; Tayfun Yörük (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The purpose of this study is to reveal the researches that deal with teleworking and technostress together with their individual, organizational and social dimensions in a holistic way within the framework of the Job Demands-Resources (JD-R) Model. In this study, a review was carried out on the Web of Science (WoS) and the Scopus databases with the assistance of bibliometric analysis techniques and the PRISMA method. The thematic content analysis method was used to reveal on which dimensions of technostress associated with teleworking and on which methods the focuses were. It can be stated that the results of the relationship analysis based on keyword frequency, performance analysis and thematic content analysis carried out within the scope of the research are consistent with each other. At this point, the findings of the research have revealed that technostress poses a dark side to teleworking as an organizational behavior challenge stemming from the COVID-19 pandemic. The current study found that teleworking-related technostress significantly affects employee well-being, with important impacts on the ISO 45003:2021 standard, and the Sustainable Development Goal 3. On the basis of being such a comprehensive and comparative research on the subject, it contributes to the relevant literature and practice.